THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDE OF STUDENTS SYIAH KUALA UNIVERSITY ABOUT THE IMPACT OF TOOTH LOSS - Andriany, Poppy; Sofya, Pocut Aya; Rahmayani, Liana; Novita, Cut Fera; Nashirah, Nanda (International Journal of Research -GRANTHAALAYAH, 2022)
Introduction, loss of teeth can cause problems with mastication, speech, aesthetics, social activities, inhibit work performance, and daily activities. Causes of tooth loss include trauma, caries, periodontal disease, infection, orthodontic treatment, and knowledge. Knowledge can influence a person & attitude. Therefore, this study aimed in cross-sectionally assessing the relationship between knowledge and attitudes of Syiah Kuala University students’ batch 2018 about the impact of tooth loss. Methods, cross-sectional study design was used in this study, involving 384 subjects, with cluster sampling technique. The results showed knowledge about the impact of tooth loss was 80.1% and attitudes about the impact of tooth loss were 79.5%. The correlation coefficient shows a positive correlation value between the knowledge and attitude variables which shows a significant level (p & lt; 0.01). Conclusion, there is a relationship between the knowledge and attitudes of Syiah Kuala University students batch the 2018 about the impact of tooth loss.